REGULATED DEGRADABILITY OF COMPOSITE BIOBASED FILMS - Isaenko, Volodymyr M.; Maritz, Alexander A.; Guy, Angela E.; Polevoy, Alexander J. (Proceedings of National Aviation University (archive), 2008)
Degradable biobased (derived from agriculture) composites are emerging materials that offer benefits to the environment thus minimizing waste that would be otherwise deposited in landfills. Single-use primary packaging materials have been identified as suitable items to be replaced by biodegradable materials from renewable resources. Materials composed of starch, soy protein and polyvinylalcohol, modified by hydrophobic fatty acids, are evaluated in terms of water resistance as promising substitutes for packaging materials.